Research progress on the application of RPA-CRISPR/Cas12a in the rapid visual detection of pathogenic microorganisms - Ji, Tuo; Fang, Xin; Gao, Yuzhi; Yu, Kun; Gao, Xuzhu (Frontiers in Cellular and Infection Microbiology, 2025)
In an increasingly complex global public health landscape, the continuous emergence of novel pathogens and the growing problem of antibiotic resistance highlight the urgent need for rapid, efficient, and precise detection technologies for pathogenic microorganisms. The innovative combination of Recombinase Polymerase Amplification (RPA) and CRISPR/Cas12a enables the rapid amplification of target gene fragments under isothermal conditions and the precise recognition and cleavage of specific nucleic acid sequences. The integration of RPA and CRISPR/Cas12a significantly enhances the sensitivity and accuracy of detection simplifies operational procedures, and reduces the dependence on specialized equipment for testing personnel. This combination demonstrates great potential for application in clinical diagnostics and point-of-care testing. This article provides a detailed overview of the principles of RPA-CRISPR/Cas12a and its latest research progress in the field of pathogen detection, aiming to promote the widespread application of RPA-CRISPR/Cas12a technology in clinical medicine and public health and to offer theoretical support for its further optimization.